Safety evaluation of the food enzyme glucose oxidase from the non‐genetically modified Aspergillus tubingensis strain GOX - EFSA Panel on Food Enzymes (FEZ); Holger Zorn; José Manuel Barat Baviera; Claudia Bolognesi; Francesco Catania; Gabriele Gadermaier; Ralf Greiner; Baltasar Mayo; Alicja Mortensen; Yrjö Henrik Roos; Marize L. M. Solano; Monika Sramkova; et al. (EFSA Journal)
Abstract The food enzyme glucose oxidase (β‐d‐glucose: oxygen 1‐oxidoreductase, i.e. EC 1.1.3.4) is produced with the non‐genetically modified Aspergillus tubingensis strain GOX by DSM Food Specialties. The food enzyme was free from viable cells of the production organism. It is intended to be used in four food manufacturing processes. Dietary exposure to the food enzyme‐total organic solids (TOS) was estimated to be up to 1.555 mg TOS/kg body weight (bw) per day in European populations. Genotoxicity tests did not indicate a safety concern. The systemic toxicity was assessed by means of a repeated dose 90‐day oral toxicity study in rats. The Panel identified a no observed adverse effect level of 2000 mg TOS/kg bw per day, the highest dose tested, which when compared with the estimated dietary exposure, resulted in a margin of exposure of at least 1286. A search for the homology of the amino acid sequence of the glucose oxidase to known allergens was made, and one match with a contact allergen was found. The Panel considered that a risk of allergic reactions upon dietary exposure to the food enzyme cannot be excluded, but the likelihood is low. Based on the data provided, the Panel concluded that this food enzyme does not give rise to safety concerns under the intended conditions of use.